155 THE CYCLIC ADENOSINE MONOPHOSPHATE RESPONSE ELEMENT BINDING PROTEIN REGULATES HEMATOPOIETIC PROGENITOR CELL PROLIFERATION AND MYELOID ENGRAFTMENT. (1st January 2005) - Kinjo, K.; Shankar, D. B.; Moore, T.; Sakamoto, K. M.
Abstract : Purpose: The cAMP response element binding protein (CREB) is a transcription factor that regulates gene expression in a variety of cell types and promotes cell proliferation and survival. We previously reported that more than 60% of AML patients overexpressed CREB in the bone marrow. To understand the role of CREB in myelopoiesis, we generated transgenic mice in which CREB is overexpressed in myeloid cells. We analyzed the hematopoietic progenitor cells from CREB transgenic mice in methylcellulose colony and bone marrow transplantation assays. Methods: Bone marrow cells obtained from hMRP8-CREB transgenic mice were plated in methylcellulose containing IL-3, IL-6, and SCF. After 14 days the colonies were counted and analyzed using FACs and cytospin preparations. Bone marrow cells (4 ×106) from CREB transgenic mice were transplanted into lethally irradiated wild type C57/BL6 recipient mice. Peripheral blood counts were obtained every 4 weeks and FACs analysis was performed. Results: CREB transgenic mice showed evidence of monocytosis, compared to age-matched littermate controls. Bone marrow cells from CREB transgenic mice formed robust colonies earlier and had increased numbers of colony forming units (CFU-GM). Bone marrow from CREB transgenic mice also had evidence of more immature myeloid cells compared to controls. We observed a 10-fold increase in the numbers of bone marrow progenitor cells from CREB transgenic mice (two different founder lines) compared to controls when cultured in the absence of cytokines. In bone marrow transplant experiments, mice transplanted with CREB transgenic mouse bone marrow had signs of earlier myeloid engraftment at 6 weeks following transplantation compared to controls. Recipients of CREB transgenic bone marrow showed increased monocytes and neutrophils in the peripheral blood with a corresponding increase in Mac-1+, Gr-1+ cell populations. The lymphocyte count was significantly lower in mice transplanted with CREB transgenic bone marrow compared to controls. Conclusions: Our results suggest that CREB plays a critical role in the regulation of normal myelopoiesis and hematopoietic progenitor cell proliferation.